2016
DOI: 10.4269/ajtmh.15-0356
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Water Treatment into Antenatal Care: Impact on Use of Maternal Health Services and Household Water Treatment by Mothers—Rural Uganda, 2013

Abstract: Abstract. To increase maternal health service use and household water treatment (HWT), free water treatment kits were provided at first antenatal care (ANC) visits and free water treatment sachet refills were provided at follow-up ANC visits, delivery, and postnatal visits in 46 health facilities in rural Uganda. We evaluated the impact by surveying 226 women in the initiative (intervention group) and 207 women who received ANC before the initiative began (comparison group). There was no differences in the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…8,43 A similar study in Uganda found only a modest increase in confirmed water treatment and no change in maternal health service use, perhaps in response to a water treatment product that was not a sufficiently desirable incentive to motivate pregnant women to attend clinic. 44 In contrast to water treatment, we found that most households had soap for handwashing at baseline, and observed a statistically significant increase from baseline to follow-up only in the percentage of mothers able to demonstrate correct handwashing technique. Similar results were observed in studies in Malawi and Kenya.…”
Section: Discussioncontrasting
confidence: 58%
“…8,43 A similar study in Uganda found only a modest increase in confirmed water treatment and no change in maternal health service use, perhaps in response to a water treatment product that was not a sufficiently desirable incentive to motivate pregnant women to attend clinic. 44 In contrast to water treatment, we found that most households had soap for handwashing at baseline, and observed a statistically significant increase from baseline to follow-up only in the percentage of mothers able to demonstrate correct handwashing technique. Similar results were observed in studies in Malawi and Kenya.…”
Section: Discussioncontrasting
confidence: 58%
“…While there are conceivable linkages between WASH and MCH services, there are few reports addressing potential benefits and challenges of integrated programming. A few, mostly small, intervention studies examined the usage of antenatal service as an entry to other public health interventions, including water treatment and hygiene education [ 13 ], or HIV testing and treatment [ 13 , 15 ]. Future operational research is needed to reveal potential benefits and challenges of integrated WASH and MCH programming.…”
Section: Discussionmentioning
confidence: 99%
“…While research has demonstrated the importance of water, sanitation, and hygiene (WASH) for maternal and child health (MCH) [ 11 , 12 ], access to improved water and sanitation facilities and use of basic MCH health services have rarely been considered together. Recently, a handful of programs that aimed to increase women’s use of antenatal care services also included water treatment [ 13 ] and hygiene education [ 14 , 15 ], pointing towards potential opportunities for MCH and WASH integrated intervention strategies in resource constraint setting.…”
Section: Introductionmentioning
confidence: 99%
“…According to the decision tree analysis, hand-washing was the most important factor in the first year of the intervention. According to the results of a previous study in Uganda, while sanitary education had a significant effect on 4 + ANC services among reproductive women, hand-washing did not [29]. We presented health education detailing the infection risks to newborns simultaneously with hand-washing education.…”
Section: Discussionmentioning
confidence: 99%
“…Enabling factor variables were selected, including promotion by radio broadcasting, source of MCH awareness (such as a community leader, signboard, radio, etc. ), distance to the health facility, RECO activities, type of delivery, and hand-washing practice [23272829]. This study selected the independent variable from among need factors such as frequency of childbirth, abortion, hand-washing, awareness of the importance of exclusive breastfeeding, ANC, delivery at health facilities, satisfaction with the services at the health facilities, and satisfaction with the health facility setting [7203031].…”
Section: Methodsmentioning
confidence: 99%